The Work of Ragnar Frisch, Econometrician - Arrow, Kenneth J. (Econometrica, 1960)
Frisch's work in all its phases exemplifies the interplay of economic theory, empirical analysis, and statistical method which peculiarly characterizes econometrics. Starting with his earliest papers, theoretical considerations have essentially the role of interpreting data. Repeatedly and in many different contexts, the need for a model, as we would say today, to enable us to learn from observations is stressed. This is particularly true when the exigencies of imperfections in data and theory lead us to statistical analysis and therewith implicitly to the admission of stochastic elements. From his empirical work, Frisch was led to examine the subtleties in the interpretation of statistical relations and the methods of statistical analysis appropriate to theoretical understanding. Such a program has inevitably meant the extensive use of mathematics, which involves two interrelated dangers: cutting the lines of communication with economists who lack mathematical training, and a tendency to value mathematical technique over economically meaningful results. In Frisch's work, the sterile Byzantinism that might be implied by these dangers is completely avoided. At all points, there is an open-minded receptivity to economic ideas derived from all sources, whether or not expressed mathematically, and the focus of all research is the underlying economic issue, not the mathematics used. This does not, however, mean any reluctance to use difficult mathematics when it is necessary to the solution. At all times, the economic problem is the master; the necessary mathematics is neither complicated for reasons of elegance and generality nor skimped for reasons of popularity. The enormous volume and variety of Frisch's work is indicated by the attached bibliography (which has been prepared by Professor Trygve Haavelmo and the University Institute of Economics, University of Oslo). This excludes (with few exceptions) his mimeographed memoranda and lectures, some of which are of the greatest importance. In reviewing his work I have been forced to be selective in a way which undoubtedly reflects my own interests and accidents of reading. No attempt has been made to discuss